2020
DOI: 10.1021/acsanm.0c01949
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Triple-Layered ZnS/ZnO/Ta2O5–SiO2 Core–Shell Nanoparticles for Enzyme-Based Electrochemical Detection of Cancer Biomarkers

Abstract: We report a methodology to fabricate unique threelayered ZnS/ZnO/Ta 2 O 5 (core)−SiO 2 (shell) nanoparticles (CSNPs) with varying compositions of ZnS, ZnO, Ta 2 O 5 , and SiO 2 in their layers (i.e., gradient structures). An electrochemical approach with better specificity and detection limit for nonneurally secreted cancer biomarker, acetylcholine (ACh), by modifying the glassy carbon electrode surface with enzyme tagged ZnS/ZnO/Ta 2 O 5 −SiO 2 CSNPs is reported. The size, composition, porosity, and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Most of the previous studies demonstrated that the bone destruction in RA was initiated by several proinflammatory cytokines produced by macrophages, such as TNF- α and IL-1 β [ 54 ]. These findings strongly correlated with the previous reports [ 20 , 55 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Most of the previous studies demonstrated that the bone destruction in RA was initiated by several proinflammatory cytokines produced by macrophages, such as TNF- α and IL-1 β [ 54 ]. These findings strongly correlated with the previous reports [ 20 , 55 ].…”
Section: Resultssupporting
confidence: 93%
“…Secondly, the subsequent transformation of ZnCl 2 to an intermediate product Zn(OH) 2 at physiological temperature leads to the formation of stable ZnO NPs at 180°C. In addition, a nonuniform transparent layer is formed by gelation on the surface of CSNPs at above 50°C, which is due to the reaction between gel and ZnO NPs [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ACh is involved in the chemical transmission at synapses and performs functions such as regulating other neurotransmitters, controlling the opening of ligand-gated ion channels, and facilitating bursts of neuronal firing . Imbalances of ACh levels have been linked to Alzheimer’s disease, myasthenia gravis, as well as behavioral, learning, and sleep disorders. Enzymatic detection of ACh has been achieved by the sequential use of acetylcholinesterase and choline oxidase to generate hydrogen peroxide from ACh. ACh quantification is then achieved by electrochemical or optical detection of the hydrogen peroxide, , but other methods have also been used. ACh has also been detected using a nickel anode electrode and electrodes that were modified with only acetylcholinesterase. So far, all of these have been carried out at micro- and macroscales.…”
Section: Introductionmentioning
confidence: 99%